2019
DOI: 10.1128/msphere.00475-19
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma brucei L11 Is Essential to Ribosome Biogenesis and Interacts with the Kinetoplastid-Specific Proteins P34 and P37

Abstract: Eukaryotic ribosome biogenesis is an essential cellular process involving tightly coordinated assembly of multiple rRNA and protein components. Much of our understanding of this pathway has come from studies performed with yeast model systems. These studies have identified critical checkpoints in the maturation of the large ribosomal subunit (LSU/60S), one of which is the proper formation and incorporation of the 5S ribonucleoprotein complex (5S RNP). Research on the 5S RNP has identified a complex containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…One possible explanation is the ribosomal protein repertoire unique to this group. It has been shown that post-transcriptional removal of additional ITSs in T. brucei is guided by ribosomal proteins [ 45 ]. In general, kinetoplastid ribosomal proteins exhibit a number of unusual features interacting with unusual rRNA [ 22 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is the ribosomal protein repertoire unique to this group. It has been shown that post-transcriptional removal of additional ITSs in T. brucei is guided by ribosomal proteins [ 45 ]. In general, kinetoplastid ribosomal proteins exhibit a number of unusual features interacting with unusual rRNA [ 22 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Alba3 might play a role in polysome formation during the stumpy to procyclic transition. Alternatively, the effect might be indirect since the Alba3KO produces less TbL11, an essential factor in ribosome maturation [58], than the parental cells. In either case, however, it would imply that only a subset of translating ribosomes are affected, since the majority of proteins are present at similar levels in both cell lines.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…2B ), with a possible bias towards the small subunit. Fourteen of the 27 small subunit proteins were found, together with 14 of the 50 large subunit proteins, including the four acidic subunits and the Kinetoplastid-specific protein NRBD2 (Jaremko et al ., 2019 ). There was no obvious link between the detection of these proteins in the pull-down, and their protein sizes or their locations on the ribosome (Jenner et al ., 2012 ).…”
Section: Resultsmentioning
confidence: 99%